2015
DOI: 10.1111/ejn.12949
|View full text |Cite
|
Sign up to set email alerts
|

Selective and divided attention modulates auditory–vocal integration in the processing of pitch feedback errors

Abstract: Speakers rapidly adjust their ongoing vocal productions to compensate for errors they hear in their auditory feedback. It is currently unclear what role attention plays in these vocal compensations. This event-related potential (ERP) study examined the influence of selective and divided attention on the vocal and cortical responses to pitch errors heard in auditory feedback regarding ongoing vocalisations. During the production of a sustained vowel, participants briefly heard their vocal pitch shifted up two s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 62 publications
2
24
0
Order By: Relevance
“…Since it has been previously shown that P2 responses become larger when participants attend to pitch feedback perturbations as compared to when they do not 49 50 , and that attentional control can be improved by working memory training 51 , one may argue that the training-related changes we observed in the N1-P2 complex were not the result of improved working memory capacities per se, but the result of an increased capacity for attentional control. That is, after working memory training, our trained participants may have paid more attention to their voice auditory feedback, and this increased attention caused the training-related changes in the N1-P2 complex.…”
Section: Discussionmentioning
confidence: 76%
“…Since it has been previously shown that P2 responses become larger when participants attend to pitch feedback perturbations as compared to when they do not 49 50 , and that attentional control can be improved by working memory training 51 , one may argue that the training-related changes we observed in the N1-P2 complex were not the result of improved working memory capacities per se, but the result of an increased capacity for attentional control. That is, after working memory training, our trained participants may have paid more attention to their voice auditory feedback, and this increased attention caused the training-related changes in the N1-P2 complex.…”
Section: Discussionmentioning
confidence: 76%
“…Moreover, multivariate logistic regression analysis revealed a lower educational level as an independent risk factor for PD-associated MSD. Several studies on the neural mechanisms underlying motor speech control [15,16,26,27] have hypothesized that a higher educational level might play a negative role in the occurrence and aggravation of PD-associated MSD. Previous MRI examinations have shown that lesions in cognitiverelevant cortical areas, especially those closely associated with educational level within the prefrontal lobe, frequently occur in SD patients [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, multivariate logistic regression analysis revealed a lower educational level as an independent risk factor for PD-associated MSD. Several studies on the neural mechanisms underlying motor speech control [15,16,26,27] have hypothesized that a higher educational level might play a negative role in the occurrence and aggravation of PD-associated MSD. Previous MRI examinations have shown that lesions in cognitiverelevant cortical areas, especially those closely associated with educational level, frequently occur in SD patients [28][29][30].…”
Section: Discussionmentioning
confidence: 99%